Development of Ethnomathematics-Based Teaching Materials through Interactive Games to Improve Students' Mathematical Literacy - Assegaff, Nurani; Bonyah, Ebeneezer (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2024)
This research explores the development of ethnomathematics-based teaching materials through interactive games, and analyzes their effectiveness in increasing students' mathematical literacy. The ethnomathematics approach combines mathematical concepts with cultural contexts and daily life practices, while interactive games provide an interesting and interactive learning experience. By applying the 4D development model (Four D model), which consists of the stages of definition, design, development, and dissemination, this research produces ethnomathematics teaching material products through interactive games for geometric transformation material. The research was conducted on class XI students majoring in Office Administration at SMK Pasundan 3 Bandung, using test and non-test instruments such as questionnaires, observation sheets, and interview guides. The research results show that the quality of teaching materials, from the feasibility aspect, falls into the very feasible category. The product of this research is ethnomathematics teaching material through interactive games for geometric transformation material. The results of this development show: (1) The quality of teaching materials seen from the feasibility aspect is included in the very feasible category; (2) ethnomathematics-based teaching materials through interactive games have a high effect on students' mathematical literacy; (3) the majority of students have a habit of mind attitude in learning after using ethnomathematics-based teaching materials through interactive games; (4) There is a correlation between mathematical literacy and students' habits of mind after using ethnomathematics teaching materials through interactive games with a strong causal relationship.